Mild solution of fractional order differential equations with not instantaneous impulses - Li Pei-Luan; Xu Chang-Jin (Open Mathematics, 2015)
In this paper, we investigate the boundary value problems of fractional order differential equations with not instantaneous impulse. By some fixed-point theorems, the existence results of mild solution are established. At last, one example is also given to illustrate the results.